1998
DOI: 10.1046/j.1365-8711.1998.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Warps in Spiral Galaxies with Massive Haloes

Abstract: A B S T R A C TWe study the persistence of warps in galactic discs in the presence of massive haloes. A disc is approximated by a set of massive rings, while a halo is represented by a conventional n-body simulation. We confirm the conclusion of Nelson & Tremaine that a halo responds strongly to an embedded precessing disc. This response invalidates the approximations made in the derivation of classical 'modified tilt' modes. We show that the response of the halo causes the line of nodes of a disc that starts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 13 publications
6
64
0
Order By: Relevance
“…Several mechanisms to trigger and maintain warps have been proposed, including tidal interactions between galaxies, inter-galactic magnetic fields, disk-halo interaction and matter accretion (see the review by Binney 1992). The forcing of a misaligned halo does not appear to be a promising solution, since the halo and disks align over a short time-scale (Nelson & Tremaine 1995;Binney et al 1998). On the contrary, galaxy interactions have been revived as an explanation, since even the prototypical isolated warped galaxy NGC 5907 has been Send offprint requests to: V. P. Reshetnikov, e-mail: resh@astro.spbu.ru found to interact with small companions (Shang et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms to trigger and maintain warps have been proposed, including tidal interactions between galaxies, inter-galactic magnetic fields, disk-halo interaction and matter accretion (see the review by Binney 1992). The forcing of a misaligned halo does not appear to be a promising solution, since the halo and disks align over a short time-scale (Nelson & Tremaine 1995;Binney et al 1998). On the contrary, galaxy interactions have been revived as an explanation, since even the prototypical isolated warped galaxy NGC 5907 has been Send offprint requests to: V. P. Reshetnikov, e-mail: resh@astro.spbu.ru found to interact with small companions (Shang et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nelson & Tremaine (1995) showed that were the inner disk misaligned with the principal plane of the flattened halo, as supposed by Sparke & Casertano (1988), its precession would be damped through dynamical friction, bringing the disk into alignment with the halo on time scales much shorter than a Hubble time. But a more compelling objection to the modified tilt mode emerged from N -body simulations with live halos: Dubinski & Kuijken (1995) found that the warp did not survive while Binney et al (1998) showed that the inner halo quickly aligns itself with the disk, not vice versa. The large store of angular momentum in the disk maintains its spin axis, but the pressure supported inner halo can readily adjust its shape slightly to align itself with the disk.…”
Section: Disks In Halosmentioning
confidence: 99%
“…For spherical systems, Eddington's formula (Binney & Tremaine 1987) can be used for this purpose. Thus, as in Binney, Jiang & Dutta (1998), we numerically calculate the halo's phase‐space distribution function from ρ h ( r ) and determine the halo particles' initial velocities according to this distribution function. For non‐spherical systems, such as the stellar disc, there is no analytical formula to be used to obtain the phase‐space distribution function directly from the density profile.…”
Section: The Modelmentioning
confidence: 99%